(untitled) (Confluenţe Bibliologice, 2016)
This article includes information about the magazine "Weat Grains” which brings together in its pages cultural history and literary articles, information about congresses, conferences, exhibitions, theatrical and musical seasons. Emanoil Bucuţa was founder and director of the magazine "Weat Grains” between 1930-1935, sociological document of real informative value. Issues of this magazines from 1931 till 1934 are kept in Rare Periodical Collection of USARB Scientiﬁc Library.